An Explanatory Analysis on Eclipse Beta-Release Bugs Through In-Process Metrics - Misirli, Ayse Tosun; Murphy, Brendan; Zimmermann, Tom; Basar, Ayse (Proceedings of the 8th International Workshop on Software Quality (WoSQ 2011), 2011)
Failures after the release of software products are expensive and time-consuming to fix. Each of these failures has different reasons pointing into different portions of code. We conduct a retrospective analysis on bugs reported after beta release of Eclipse versions. Our objective is to investigate what went wrong during the development process. We identify six in-process metrics that have explanatory effects on beta-release bugs. We conduct statistical analyses to check relationships between files and metrics. Our results show that files with beta-release bugs have different characteristics in terms of in-process metrics. Those bugs are specifically concentrated on Eclipse files with little activity: few edits by few committers. We suggest that in-process metrics should be investigated individually to identify beta-release bugs. Companies may benefit from such a retrospective analysis to understand characteristics of failures. Corrective actions can be taken earlier in the process to avoid similar failures in future releases.